2009
DOI: 10.1016/j.brainres.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of neuroendocrine stress responses to acute ferret odor by medial, but not central amygdala lesions in rats

Abstract: Investigations of the neural pathways associated with responses to predators have implicated the medial amygdala (MeA) as an important region involved in defensive behaviors. To our knowledge, however, the involvement of the MeA in neuroendocrine responses to predator odor exposure has not been investigated. Therefore, the present study examined the effects of MeA disruption in rats exposed to ferret or control odor on hypothalamo-pituitary-adrenocortical (HPA) axis activation. Bilateral lesions of the MeA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
5
17
0
Order By: Relevance
“…In contrast, our current study showed no increase in c-Fos expression in CRF-containing neurons with EPM exposure. Several prior studies which investigated the effect of lesions to the CEA showed no role in the mediation of unconditioned anxiety to predator odor [5052]. This supports our own data which demonstrated no activation of CRF-containing neurons in subdivisions of the CEA following predator odor stress.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, our current study showed no increase in c-Fos expression in CRF-containing neurons with EPM exposure. Several prior studies which investigated the effect of lesions to the CEA showed no role in the mediation of unconditioned anxiety to predator odor [5052]. This supports our own data which demonstrated no activation of CRF-containing neurons in subdivisions of the CEA following predator odor stress.…”
Section: Discussionsupporting
confidence: 90%
“…The increase in aversive behaviors in rats upon exposure to a ferret odor corroborates a number of previous studies which showed similar behavioral effects (Masini et al, 2005, Masini et al, 2006, for review see Campeau et al, 2008, Wilson and Junor, 2008, Masini et al, 2009, Weinberg et al, 2009, Masini et al, 2010). Olfactory receptors which are specific to predator threats are processed by unique zones in the olfactory bulb (Kobayakawa et al, 2007), which project to and activate limbic brain regions such as the amygdala following exposure to predator odors (Hebb et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies by Staples et al (2006, 2008b) and others have suggested little to no avoidance behaviors in rats exposed to TMT. The olfactory bulb projects to the amygdala and recent evidence suggests that the MEA plays a prominent role in the expression of aversive behaviors following exposure to ferret odor as lesions to the MEA disrupted hypothalamo-pituitary-adrenocortical axis activation following ferret odor exposure – an effect not observed with CEA lesions (Masini et al, 2009). However, we have previously shown that the CEA can regulate rat aversive behaviors to ferret odor through opioid-dependent mechanisms (Wilson and Junor, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…B: scatterplot depicting the timing of the peak response to cat urine of all recorded units and the mean Ϯ SE timing of the response peak to cat urine in the MeAV (n ϭ 7), MePV (n ϭ 21), MeAD (n ϭ 16), MePD (n ϭ 28), CoA (n ϭ 7), BLa and BLv (n ϭ 4 each), BMa (n ϭ 6), BMp (n ϭ 10), AHi (n ϭ 13), CeM (n ϭ 3), and BSTIA (n ϭ 8 1995) and is the first site of olfactory convergence (Meredith 1998), it is in an excellent position to integrate olfactory cues signaling predators and engage excitatory or inhibitory events in downstream targets that regulate defensive responses. These findings are consonant with gene activation studies Meredith and Westberry 2004) and converge with lesion studies (Li et al 2004;Masini et al 2009) to highlight the critical involvement of the MeA in predator odor-generated fear.…”
Section: Discussionsupporting
confidence: 81%